2016
DOI: 10.1016/j.jocn.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative real-time MRI-guided stereotactic biopsy followed by laser thermal ablation for progressive brain metastases after radiosurgery

Abstract: Stereotactic radiosurgery is one of the treatment options for brain metastases. However, there are patients who will progress after radiosurgery. One of the potential treatments for this subset of patients is laser ablation. Image-guided stereotactic biopsy is important to determine histopathological nature of the lesion. However, this is usually based on preoperative, static images, which may affect the target accuracy during the actual procedure as a result of brain shift. We therefore performed real-time iM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…3 While only 3 of the 4 patients had complete lesional treatment, all had improvement in their KPS score 3 months after surgery. Since then, several other investigators have detailed their experience (single cases or case series) and have described variable success with LITT for the treatment of both biopsy-proven regrowing tumor 8,19,20 and biopsy-proven RN. 4,11,16 Therefore, the current study was performed to prospectively determine the safety, efficacy, and outcome of LITT for regrowing SRS-treated lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 While only 3 of the 4 patients had complete lesional treatment, all had improvement in their KPS score 3 months after surgery. Since then, several other investigators have detailed their experience (single cases or case series) and have described variable success with LITT for the treatment of both biopsy-proven regrowing tumor 8,19,20 and biopsy-proven RN. 4,11,16 Therefore, the current study was performed to prospectively determine the safety, efficacy, and outcome of LITT for regrowing SRS-treated lesions.…”
Section: Discussionmentioning
confidence: 99%
“…17 Anecdotally, the option of MRI-guided laser interstitial thermal therapy (LITT) has been effective for the treatment of both pathological entities after SRS when craniotomy is not feasible because of either lesion location or concerns regarding medical comorbidities. 1,3,6,11,12,14,19,20 Results from a phase I clinical trial using the NeuroBlate system (Monteris Medical Inc.) showed that the device provides neurosurgeons with a minimally invasive surgical option for tumor ablation. 15 An earlier study in 16 glioblastoma patients suggested that LITT offers a survival advantage over medical management or chemotherapy alone.…”
mentioning
confidence: 99%
“…The studies discussed in this review comprise only biopsy-confirmed cases of RN. However, many have argued that recurrent lesions after prior SRS for brain metastases may represent a mixture of both radiation necrosis and recurrent tumor pathologies, subject to local sampling bias and thus minimizing the diagnostic accuracy of intraoperative biopsy [41][42][43]. While the aforementioned studies suggest LITT may result in similar peri-procedural outcomes in terms of overall symptom improvement and steroid weaning, the underlying pathology has significant implications.…”
Section: Discussionmentioning
confidence: 99%
“…While traditionally the workflow for LITT involved stereotactic placement of the laser in the OR and then either patient transfer to an MRI scanner 4 or utilization of intraoperative MRI, 16 we believe there are advantages to performing the entire procedure in the MRI suite. We examined our initial institutional experience with the realtime MRI system for laser amygdalohippocampal ablation and found that the initial learning curve can be quickly mastered.…”
Section: Discussionmentioning
confidence: 99%